1997
DOI: 10.1006/viro.1997.8582
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Induction of Multiple Cytokines by Human Respiratory Syncytial Virus Requires Activation of NF-κB and Is Inhibited by Sodium Salicylate and Aspirin

Abstract: Infection of the lung epithelial cell line A549 by respiratory syncytial virus (RSV) resulted in the elevated synthesis of multiple cellular cytokines, including a number of interleukins (ILs). Detailed studies of IL-11 induction revealed that it required infection by viable virus and involved a net increase in the steady state level of IL-11 mRNA. Nuclear run-on assays showed a direct effect of RSV on IL-11 gene transcription. Mutational analysis of the IL-11 promoter fused to a reporter luciferase gene demon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
129
0
2

Year Published

1998
1998
2013
2013

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 140 publications
(138 citation statements)
references
References 51 publications
7
129
0
2
Order By: Relevance
“…To investigate the role of NF-nB in bone tumor burden and associated tumormediated osteolysis, a recombinant retrovirus containing a mInB expression cassette and a neomycin drug resistance marker were used to generate cells that stably express the mInB. The mInB cassette was mutated by replacing Ser 32 and Ser 36 with alanines. The mInB binds NF-nB, but because the mInB cannot be phosphorylated at two key sites NF-nB signal transduction is suppressed.…”
Section: Resultsmentioning
confidence: 99%
“…To investigate the role of NF-nB in bone tumor burden and associated tumormediated osteolysis, a recombinant retrovirus containing a mInB expression cassette and a neomycin drug resistance marker were used to generate cells that stably express the mInB. The mInB cassette was mutated by replacing Ser 32 and Ser 36 with alanines. The mInB binds NF-nB, but because the mInB cannot be phosphorylated at two key sites NF-nB signal transduction is suppressed.…”
Section: Resultsmentioning
confidence: 99%
“…Engagement of TLR4 initiates an intracellular signaling cascade leading to activation of transcription factors responsible for initiation of transcription of proinflammatory genes. NF-B is central to expression of most of these genes (22,23). In resting cells, NF-B is sequestered in the cytoplasm by interaction with the IB (inhibitor of NF-B) family of inhibitory proteins.…”
Section: Reduced Ib␣ Phosphorylation In Pbmc From Patients Heterozygomentioning
confidence: 99%
“…Furthermore, in mammalian and plant cells, this compound has been reported to impact intracellular signaling processes and the cytokine network (6,7). We recently showed that treatment of an invasive experimental S. aureus infection (endocarditis) with intravenous aspirin caused a significant reduction in bacterial densities within target tissues (vegetations and kidneys), and that these effects are mediated by salicylic acid (8).…”
Section: Introductionmentioning
confidence: 99%